Noodles on a bicycle - Maclear, Kyo, 1970- (Random House Studio, 2024)
Children watch in amazement as the bicycle food deliverers of Tokyo stack their noodle bowls like architects, zip through the city like acrobats, and deliver delicious noodles to students, office workers, and families.